Should Surgical Services Admit Small Bowel Obstructions Managed Non-operatively?. Issue 8 (August 2022) - Thacker, Christopher; Lauer, Claire; Nealon, Kathleen; Wang, Shengxuan; Factor, Matthew
Introduction: Over the past decade, small bowel obstructions (SBO) have been increasingly managed non-operatively. Prior studies have looked at outcomes based on admission to surgical services (SS) or medicine services (MS), but most are restricted to operative patients. This study evaluates the outcomes of non-operative patients specifically. Methods: A 12-year retrospective cohort study of patients ≥18-years-old admitted with SBO within one healthcare system was performed. Only non-operative patients were included. Clinicodemographic characteristics and admission details were extracted from the electronic medical record. Statistical analysis was performed using the student's t-test, chi-square, and multivariable regression. Results: A total of 3278 patients were included, of which 933(28.4%) patients were admitted to a SS. MS patients were older (57.7 vs 54.7 years, P < .001) and more likely to have diabetes (24.1 vs 20.2%, P = .015), CHF (5.7 vs 3.1%, P = .002), and AKI (29.8 vs 16.7%, P < .001). SS patients were more likely to have cancer (19.3 vs 13.7%, P < .001). Univariate analysis showed admission to SS decreased length of stay (3.4 vs 4.1 days, P < .001) and index admission mortality (0.1 vs 2.2%, P < .001). On multivariable analysis, admission to a SS decreased admission mortality (OR 0.056), 30-day mortality (OR 0.15), and 180-day mortality (OR 0.307). Similarly, 30-day readmissions (OR 0.683) and 180-day readmission (OR 0.54) were also significantly decreased. Length of stay was decreased by .6 days ( P < .001). Discussion: In patients with non-operative SBO, admission to a surgical service decreased length of stay, mortality, and readmission. Further work should be completed evaluating how increased comorbidities affect long term outcomes. However, significantly decreased length of stay and mortality continue to support surgical services admitting SBO patients.